Peningkatan Kemampuan Teknis Pelaku Konstruksi di Kabupaten Fakfak Melalui Klinik Perancangan Beton Normal: Improving Technical Skills of Construction Practitioners in Fakfak Regency Through Normal Concrete Design Clinic - Attamimi, Aqilah; Imran (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2024)
In regional infrastructure development activities, concrete mix design is a crucial aspect that must be mastered to ensure construction projects are carried out according to plan, meeting cost, quality, and time targets effectively and efficiently, while also being accountable. CV. Marapi Jaya, a construction service company operating in Fakfak Regency, serves as a partner in this Community Service initiative. CV. Marapi Jaya, along with local participants, will be guided and trained through the activity titled Enhancing Technical Skills of Construction Practitioners in Fakfak Regency Through Normal Concrete Design Clinic.The training employs a learning by doing method, focusing on concrete mix design procedures in compliance with SNI (Indonesian National Standard). The materials provided to participants include: an introduction to SNI methods and its design components, calculations for normal concrete mix design, and estimation of material requirements. At the end of the training, participants will receive practical sessions on designing normal concrete mixes and their components.Through this clinic, aligned with SNI standards, the program aims to improve the understanding and skills of participants, including staff from CV. Marapi Jaya and groups of indigenous Papuans engaged in construction services. The outcomes of this community service activity include a publication in an accredited SINTA 6 journal and an article in print or electronic local media documenting the event